(untitled) (Journal of the College of Basic Education, 2022)
This study is an attempt to reveal some of the most important administrative problems facing the heads of scientific departments through a tool that was built according to the procedures for building educational and psychological standards, by identifying the areas that make up the behavioral domain (administrative problems), so it was six areas, (60) paragraphs were formulated Distributed evenly over the fields by (10) paragraphs for each field and according to the Likert method of answering, the standard characteristics (honesty, reliability) of the scale were verified. 270) The head of the department was chosen in a simple random way, and it was applied during the academic year 2014-2015, and the study reached important results that were analyzed and discussed according to the fields of study.